Pengaruh Kualitas Audit, Audit Report Lag, Manajemen Laba Dan Financial Distress Terhadap Opini Audit Going Concren Pada Perusahaan Property Real Estate 2018-2020 Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Indah Lia Puspita; Siti Nurjannah (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
The purpose of this study is to find out whether audit quality, audit report lag, manajemen laba and financial distress can affect going concren oppinions during the 2018- 2020 period in property and real estate sub-sector companies. This study uses secondary data obtained from company auditor reports taken on the Indonesia Stock Exchange website or www.idx.co.id. In this study, there were 159 companies studied during the 2018-2020 period. The test results in the hypothesis used are logistic regression analysis which results that audit quality does not affect going concernaudit opinion while audit lag affects going concern audit opinion.